2022
DOI: 10.1136/bmjopen-2021-055017
|View full text |Cite
|
Sign up to set email alerts
|

Status of hospital-based blood transfusion services in low-income and middle-income countries: a cross-sectional international survey

Abstract: ObjectivesBlood transfusion is life-saving for patients experiencing acute blood loss and severe anaemia. In low-income and middle-income countries (LMICs), low blood donation rates and unavailability of whole blood and blood components (blood products) impairs timely blood transfusion. To fulfil patient-specific blood orders, a hospital blood transfusion service (HBTS) receives orders from a prescriber for blood transfusion, tests and prepares blood products for the patient. This study sought to describe the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
(103 reference statements)
0
8
0
1
Order By: Relevance
“…Using data and samples collected as part of the REDS-III program, the study [32] investigated how the metabolism of stored RBCs is impacted by the heterogeneity of blood processing and storage additives at different centers, emphasizing the crucial role of standardization in blood processing and storage to minimize the variability of blood products across different centers. The relative abundance of metabolites (energy metabolism, amino acids, and nucleotides) in RBCs stored for varying durations (1,7,14,21,28, and 42 days) from three different centers is shown in Figure 2. The figure highlights the importance of standardizing blood processing and storage procedures to reduce heterogeneity between centers.…”
Section: Big Data In Transfusion Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Using data and samples collected as part of the REDS-III program, the study [32] investigated how the metabolism of stored RBCs is impacted by the heterogeneity of blood processing and storage additives at different centers, emphasizing the crucial role of standardization in blood processing and storage to minimize the variability of blood products across different centers. The relative abundance of metabolites (energy metabolism, amino acids, and nucleotides) in RBCs stored for varying durations (1,7,14,21,28, and 42 days) from three different centers is shown in Figure 2. The figure highlights the importance of standardizing blood processing and storage procedures to reduce heterogeneity between centers.…”
Section: Big Data In Transfusion Medicinementioning
confidence: 99%
“…This is of particular importance since there is a shortage of blood products all over the world, e.g., [19]. Although quality control per se does not increase the total amount of blood products, a need which is even increased with the COVID-19 pandemic [20, 21], transfusion product management concepts, and putative increased shelf life (at least for a fraction of the donors) may ensure the most effective application for each blood donation (including a best donor-patient match). Artificial intelligence (AI) has emerged as a promising method to access and analyze such parameters providing valuable insights into single RBC quality and function [22].…”
Section: Introductionmentioning
confidence: 99%
“…The Gambia (n = 1) 1 (100%) 1 (100%) recruitment methods to include self-identifying donors (25, 54%) and hospital requirements for patients or family members to supply or replace blood transfused (family or replacement donations) (15, 33%). 13 Notably, directed and replacement donors are disincentivized to admit any high-risk behavior, which contributes to the risk of TTIs. Transfusion-associated graft-versus-host disease (TA-GVHD) is another theoretical risk of directed donations from relatives 14 that is poorly characterized in low-income settings/SSA.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with existing literature that transfusion services, particularly in SSA, experience chronic shortages of blood and often have hospital‐based models of blood collection to support emergent needs 7 . For example, in a study of 50 hospital blood transfusion services in low‐income and middle‐income countries, including 13 responses from eight countries in SSA, Barnes et al found that 77% of transfusion services (36 of 47) reported performing onsite blood collections to meet blood transfusion needs; 15 of these transfusion services were solely dependent on blood collected onsite 13 . We found that among institutions that collect blood onsite, patients' family members are the most common donor source, although it is not known from survey respondents whether the products collected from relatives are intended for the index patient or for the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Preserva Sangue voltado para incentivar o Patient Blood Management (Hemoce, 2022); um conjunto de abordagens multidisciplinares baseadas em evidências cujo objetivo é uma prática conservadora da transfusão sanguínea, dentro e fora do ambiente hospitalar, para melhores resultados médicos e cirúrgicos para o paciente; essas práticas são ainda mais relevantes em contextos de países de baixa renda(Meybohm et al, 2017; Muñoz et al, 2019; Sabm, 2019;Barnes et al, 2022).Poucos tangenciam de fato a área de gestão como o The Blood Bank Information System, que permite aos administradores atualizarem suas informações de inventário de sangue disponíveis e visualizar a relação de doadores disponíveis no sistema, além de enviar uma notificação para eles em situações de emergência ou de estoque baixo(Kayode et al, 2019). Uma criação nacional é o SIHemo, concebido no Hospital das Clínicas da Universidade Federal de Minas Gerais, com a sua implementação é possível criar artifícios para a identificação de receptores e hemocomponentes, otimizar a gestão do estoque, diminuir o descarte dos produtos sanguíneos pela perda de validade, reduzir gastos, rastreamento de ações através do uso de senhas individuais, análise da movimentação das bolsas de sangue e otimização da gestão de trabalhadores e do número de testes de laboratoriais.Até onde os autores sabem por meio de pesquisas na literatura, acredita-se que o Banco de Sangue seja o primeiro aplicativo criado, voltado para a área de condutas hemoterápicas em procedimentos cirúrgicos.…”
unclassified